What is the underlying structure of the climate, conflict, and socio-economic system in Mali? A network analysis - Basel, Ashleigh Megan; Onivola Minoarivelo, Henintsoa; Craparo, Alessandro Carmelo William; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Mali, using network analysis. Results show that poverty is inextricably linked to conflict in Mali and importantly, is very strongly driven by the heavy dependancy on temperature sensitive agriculture.